Cascade size and dose rate effects on α′ precipitation in ion-irradiated Fe14Cr alloy. (November 2019) - Harrison, R.W.; Carruthers, A.W.; Hinks, J.A.; Burke, M.G.; Donnelly, S.E.
Abstract: Dose rate and cascade size effects on α′ formation in Fe14Cr have been studied under ion irradiation using analytical scanning transmission electron microscopy. Samples were irradiated with 100 keV He, 350 keV Ne or 1 MeV Kr ions at 300 °C to a dose of 2.5 DPA at dose rates of 10 −4 and 10 −3 displacements per atom (DPA)/s. Higher dose rates commensurately accelerate α′ precipitation under He ion irradiation, resulting in similar precipitate sizes and density. Number densities of α′ precipitates decreased with increasing ion mass and energy attributed to ballistic mixing from high-energy-density cascade formation and sub-cascade overlap. Graphical abstract: Unlabelled Image